Study on Primary Percutaneous Coronary Intervention (PCI) in Patient with Acute Myocardial Infarction: In-Hospital and 30-days Survival Outcome (Cardiovascular Journal, 2010)
Objective: Aim of our study was to evaluate the safety and survival outcome of Primary PCI (pPCI) in patients with Acute Myocardial infarction in our hospital setting. Methods: Total 30 (Female 5; Male 25) patients were enrolled in this study who were brought in to our hospital with STEMI. Average age was, Male 56, Female 52. Primary PCI was performed after transferring patient from Emergency Department (ED) to Cardiac Catheterization laboratory. Cardiovascular risk factors among the studied population were Dyslipidemia, Diabetes Mellitus, Hypertension, Smoking and Family History. Results: Primary PCI either with Bare Metal Stent (BMS) or Drug Eluting Stent (Sirolimus-eluting stent or Paclitaxel stent) were performed in total 13 LAD lesion and 15 RCA lesion and 2 LCX lesion. BMS used were 66.7%, Sirolimus 20% and Paclitaxel-eluting stent 13.3%. Total 2 patients expired but due to hemorrhagic CVA and refractory heart failure. At presentation, ECG evidenced diagnosis were Acute Anterior Wall MI : 12 (40%), Inferior MI: 16 (53%), Infero-Posterior MI: 2 (6.7%). Our study showed that Primary PCI increases the higher survival outcome 28 (93.3%) out of 30 patients with acute MI. Conclusion: Our present study revealed that revascularization by Primary PCI showed safety and better percentage of In-hospital and 30-days survival outcome in patients with Acute myocardial infarction in our hospital setting. Keywords: Primary PCI; STEMI. DOI: 10.3329/cardio.v2i2.6641Cardiovasc. j. 2010; 2(2) : 212-217